Does the nitrogen application associated with Azospirillum brasilense inoculation influence corn nutrition and yield? - Souza, Elton M. de; Galindo, Fernando S. [UNESP]; Teixeira Filho, Marcelo C. M. [UNESP]; Silva, Paulo R. T. da [UNESP]; Santos, Arthur C. dos; Fernandes, Guilherme C. [UNESP] (Univ Federal Campina Grande, 2019)
The aim of this study was to investigate the synergistic effect between inoculation with Azospirillum brasilense and nitrogen application, thus enabling a higher efficiency of nitrogen fertilization, as evaluated by nutritional value, components production, and grain yield of irrigated corn. The experiment was conducted in Selviria, MS, Brazil, under a no-till system, on an Oxisol in the Brazilian Cerrado. The experiment was set up in a randomized block design with four replications, in a 4 x 2 factorial arrangement: four patterns of nitrogen application [application of 30 kg ha(-1) of N at sowing and 150 kg ha(-1) as cover (30 + 150); 30 kg ha(-1) of N at sowing, split into two applications of 75 kg ha(-1) as cover (30 + 75 + 75); 180 kg ha(-1) of N at sowing (180); and 150 kg ha(-1) of N at sowing and 30 kg ha(-1) as cover (150 + 30)]; with and without inoculation of the seeds with A. brasilense. The application of 30 kg ha(-1) of N at sowing and a single application of 150 kg ha(-1) or two applications of 75 kg ha(-1) in topdressing, inoculated with Azospirillum brasilense provided better nutrition and development, with a positive reflection on irrigated corn grain yield in the Brazilian Cerrado.
Keywords: Lea mays; biological nitrogen fixation in grasses; bacteria promoting of plant growth; nitrogen fertilization management